7=-7-(p-8)

Simple and best practice solution for 7=-7-(p-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7=-7-(p-8) equation:


Simplifying
7 = -7 + -1(p + -8)

Reorder the terms:
7 = -7 + -1(-8 + p)
7 = -7 + (-8 * -1 + p * -1)
7 = -7 + (8 + -1p)

Combine like terms: -7 + 8 = 1
7 = 1 + -1p

Solving
7 = 1 + -1p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add 'p' to each side of the equation.
7 + p = 1 + -1p + p

Combine like terms: -1p + p = 0
7 + p = 1 + 0
7 + p = 1

Add '-7' to each side of the equation.
7 + -7 + p = 1 + -7

Combine like terms: 7 + -7 = 0
0 + p = 1 + -7
p = 1 + -7

Combine like terms: 1 + -7 = -6
p = -6

Simplifying
p = -6

See similar equations:

| 8x+0.5=7x+2 | | 2m+13=25 | | 19m+9n=16 | | 2x+4=4x+16 | | 5x+12=-42-4x | | 9=q-4 | | 5(f-9)=-45 | | n/3-6=10 | | 4x+5=-2+2 | | 9=a-4 | | 8(s-6)=-100 | | y/-23 | | 2(x^2+4)=0 | | 2P(A)=P(B)=5/13 | | 64p=16 | | A=3(a*a)*5a+7(a*a)*2a+7 | | 2P(A)=5/13 | | -10-3x-5x=-42 | | 70=5(4i+2) | | T+32=420 | | 2*n-(n-7)=12 | | 3(t+2)=-9 | | 0.602=j-4.75 | | 3x+2(x+1)=2x+12 | | -6x+10+2x=.22 | | 4ix=6i | | 5x-2y-9z=13 | | 7k-35=24-3k | | 3Z/7-3=-2 | | 49*3-3*(12)= | | -2+6x+2x=.2 | | -45=5s |

Equations solver categories